The World of Ibn Taymiyya: An Analysis of the Historical Context of Ibn Taymiyya’s Anti-Mongol Fatwas - DeVoogd, Jarod (AUC Knowledge Fountain, 2023)
Studies into Ibn Taymiyya’s fatwas against the Mongols are relatively new, despite the increasing frequency with which they are cited by modern extremist groups. Detailed explorations into the Mamluk-Ilkhanid War of the late thirteenth and early fourteenth century are also relatively new. Ibn Taymiyya, the early Mamluk Sultanate, and the Mamluk-Ilkhanid War are intricately connected, yet they are often not studied in synthesis. Generally, works that give overviews of the history of this period lack intricate details, studies dedicated to in-depth analysis of specific events are not focused on a connection to Ibn Taymiyya’s writings, and biographies on Ibn Taymiyya or works that focus on a particular aspect of his thought lack an incorporation of the historical details. Therefore, this study aims to explore and illuminate explicit linkages between actions and rulings of Ibn Taymiyya, particularly those related to war against the Mongols, with historical events of his time. Through a more thorough synthesis of historical events and Ibn Taymiyya’s life in this thesis, it will become increasingly apparent how the terms of his fatwas against the Mongols were prescribed to address very specific time and place contexts. This will provide an insightful look into the past while also providing a starting point for understanding those who invoke Ibn Taymiyya in our time.